Where We Stand: The University of Minnesota and Dakhóta Treaty Lands - Čhaŋtémaza (Neil McKay) and Monica Siems McKay (Open Rivers, 2020)

(untitled)
Despite the centuries-long and ongoing erasure of Indigenous peoples from American history textbooks and classrooms, and the chronic consignment of Indigenous peoples to the past in mainstream American consciousness, it remains a fact that every inch of what is now the United States is land to which one or more Indigenous nations has a deep and abiding connection, and of which, at some point, the U.S. government at least tacitly acknowledged Indigenous ownership.